2021
DOI: 10.1161/circulationaha.120.051718
|View full text |Cite
|
Sign up to set email alerts
|

Emulating Randomized Clinical Trials With Nonrandomized Real-World Evidence Studies

Abstract: Background: Regulators are evaluating the use of non-interventional real-world evidence (RWE) studies to assess the effectiveness of medical products. The RCT-DUPLICATE initiative uses a structured process to design RWE studies emulating randomized controlled trials (RCTs) and compare results. Here, we report findings of the first 10 trial emulations, evaluating cardiovascular outcomes of antidiabetic or antiplatelet medications. Methods: We selected 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
175
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 216 publications
(200 citation statements)
references
References 46 publications
8
175
1
3
Order By: Relevance
“…A recent meta-epidemiological study conducted by IMPACT-HTA work package six consortium found no evidence of a systematic difference in treatment effects for pharmaceutical interventions but substantial variation in these differences for specific clinical questions. Similar results were observed among the first ten trial emulations from the RCT-DUPLICATE project in which RCTs were replicated in US claims databases [17]. There is stronger evidence that nonrandomized studies relying on external controls, such as single-arm trials, are associated with greater bias on average than other types of nonrandomized studies [16].…”
Section: The Use Of Nonrandomized Evidence To Estimate Treatment Effectssupporting
confidence: 60%
“…A recent meta-epidemiological study conducted by IMPACT-HTA work package six consortium found no evidence of a systematic difference in treatment effects for pharmaceutical interventions but substantial variation in these differences for specific clinical questions. Similar results were observed among the first ten trial emulations from the RCT-DUPLICATE project in which RCTs were replicated in US claims databases [17]. There is stronger evidence that nonrandomized studies relying on external controls, such as single-arm trials, are associated with greater bias on average than other types of nonrandomized studies [16].…”
Section: The Use Of Nonrandomized Evidence To Estimate Treatment Effectssupporting
confidence: 60%
“…Emerging evidence from the COVID-19 pandemic suggests that individuals with type 2 diabetes comprise a significant portion of the affected population and are at higher risk for severe outcomes including hospitalization and death (1,2). Due to the lack of a were selected as an active comparator because they are branded agents that have been well studied with minimal other clinical effects of concern, are among the five second-line therapies with prevalent use (17), and were recently suggested as an optimal comparator as a relatively newer agent among second-line therapies (18).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from the randomized controlled trial (RCT)-DUPLICATE initiative reported the findings from the first ten trial emulations evaluating cardiovascular outcomes of antidiabetic or antiplatelet medications using RWD from three US healthcare claims data sources [3]. Patients were selected according to corresponding RCT inclusion/exclusion criteria, and end points similarly matched in claims data.…”
Section: Rwe Initiative Relating To Hta: Rct-duplicatementioning
confidence: 99%
“…Given the body of evidence presented to regulators typically forms the core of that subsequently presented to HTA bodies and payers, it is vital that those involved in HTA/market access remain aware of these developments and proactively consider any potential impact for HTA. The outcomes from Franklin et al, however, may not translate directly into outcomes that would be important for HTA decisions [3]. For example, the measure of 'regulatory agreement' may not translate into a similar concept of 'HTA agreement', as HTA bodies are more concerned with the magnitude of effect and implications for cost-effectiveness estimates rather than simply the existence and direction of an effect.…”
Section: Rwe Initiative Relating To Hta: Rct-duplicatementioning
confidence: 99%